1996
DOI: 10.1177/144078339603200304
|View full text |Cite
|
Sign up to set email alerts
|

Money in heterosexual relationships

Abstract: Money in middle-income Anglo-Celtic marriage is joint and nebulous, whereas money in cohabiting heterosexual relationships is separate and calculable. The move from cohabitation to marriage is accompanied by greater jointness in the management of money. As the nature of the couple's commitment becomes more explicit in marriage, money becomes more nebulous and less calculable. However, in both marriage and cohabitation, the questions of equality, power and control are blocked so that the reality of women's lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
69
0
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(75 citation statements)
references
References 5 publications
5
69
0
1
Order By: Relevance
“…All in all, studies on changes from an independent money management system to joint pooling are rather scarce and do not provide clear empirical evidence, as shown for the non-representative, qualitative studies on marriage, for example Burgoyne et al (2010) and Singh and Lindsay (1996), where the number of observed marriages was small. There is no evidence available on the effect of childbirth on money management systems.…”
Section: Research On Money Management Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…All in all, studies on changes from an independent money management system to joint pooling are rather scarce and do not provide clear empirical evidence, as shown for the non-representative, qualitative studies on marriage, for example Burgoyne et al (2010) and Singh and Lindsay (1996), where the number of observed marriages was small. There is no evidence available on the effect of childbirth on money management systems.…”
Section: Research On Money Management Systemsmentioning
confidence: 99%
“…Cohabitation money is highly individualised and kept separate, as shown by various studies (e.g., Vogler, 2005;Vogler et al, 2006). In contrast, the majority of married couples have been found to pool their incomes (Heimdal and Houseknecht, 2003;Lauer and Yodanis, 2011) and organise 'marriage money', which is joint but also nebulous (Singh and Lindsay, 1996). Besides marriage, childbirth is another expression of commitment to the relationship and also makes joint investments necessary.…”
Section: Marriage Childbirth and Partners' Resourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…2006) ; en Nouvelle-Zélande (Elizabeth, 2001), en Norvège (Lyngstad et collab. 2011) ; au Danemark et en Espagne (Hamplová et Le Bourdais, 2009) et en Australie (Singh et Lindsay, 1996). Trois explications à ce phénomène sont géné-ralement évoquées.…”
Section: Modes De Gestion Selon L'état Matrimonial : Revue De La Littunclassified
“…Such a finding is in line with expectations. As the nature of a couple's commitment becomes more explicit in marriage, resources are often pooled (Singh and Lindsay, 1996). Hence, home-ownership, which often leads to the pooling of resources, may be viewed as a sign of commitment.…”
Section: <>mentioning
confidence: 99%